Metformin for primary prevention of colorectal neoplasms in adenoma-free populations: a systematic review and dose-response meta-analysis - Shen, Mengdan; Lu, Shan; Xu, Zihao; Zhou, Feifei; Sheng, Li-Ting; Yu, Qiang (Frontiers in Pharmacology, 2025)
BackgroundMetformin shows promise in preventing colorectal cancer (CRC) and its precursors, but evidence on its dose-response effect remains limited.AimTo determine the association between metformin therapy and colorectal neoplasms in adenoma-free individuals and characterize the dose-response relationship.MethodsAdjusted effect estimates from each study were aggregated using a random-effect model. Subgroup analyses, publication bias assessment, sensitivity analyses and dose-response analyses were conducted.ResultsA total of 37 eligible studies, involving 1,416,085 participants, were included. Metformin significantly reduced colorectal neoplasms risk (Hazard ratio (HR) = 0.79, 95% confidence interval (CI), 0.73–0.85, Odds ratio (OR) = 0.80, 95% confidence interval, 0.74–0.87). Subgroup analyses demonstrated enhanced efficacy in Asian populations, younger patients (<60 years), and cohorts with ≥50% male participants. Dose-response analysis identified 331 mg/day as the optimal dose for CRC risk reduction (OR = 0.83, 95% CI, 0.76–0.91). Each additional year of use reduced CRC risk by 3% (OR = 0.97, 95% CI, 0.95–0.99).ConclusionMetformin demonstrates effective chemoprevention against colorectal neoplasms, where the inverse association was most prominent at low-dose, long-term therapy.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, Identifier CRD42023394042.